The Humanistic Education Model in Virtual Learning During Covid-19 Pandemic - Mansir, Firman (Universitas Negeri Malang, 2022)
Humanistic education conceptually can build peace of mind and body to achieve the virtues of a learner's life. The perfection of this life can be directed to the development of personality that includes thinking, mental strength and creativity of students by developing patterns of individual human development. The concept of humanization and the nature of education is the element that can best distinguish humans by using their thoughts because this is a gift of reason that has been given by the creator. In addition, humans are free to use it through the learning process. This research used a qualitative approach and literature analysis as a method of data analysis. Thus, to respond to virtual learning during the COVID-19 pandemic, it is necessary to prioritize and apply education and methods that are better able to understand the human condition as learners. It is expected that through this process, general educational goals can be achieved and specific learning objectives can be realized. Model Pendidikan Humanis dalam Pembelajaran Virtual di Masa Pandemi Covid-19Pendidikan humanis secara konseptual dapat membangun ketenangan jiwa dan raga untuk mencapai keutamaan kehidupan pembelajar. Kesempurnaan kehidupan ini bisa diarahkan kepada pengembangan kepribadian yang mencakup pemikiran, kekuatan jiwa dan kreativitas peserta didik dengan cara dapat mengembangkan pola pengembangan individual manusia. Hasil penelitian ini menunjukkan bahwa konsep humanisasi dan hakikat Pendidikan merupakan unsur yang paling bisa membedakan manusia dengan menggunakan pemikirannya, lantaran ini adalah anugerah nalar yang sudah diberikan sang pencipta dan manusia bebas memanfaatkannya melewati proses pembelajaran khususnya pembelajaran online. Penelitian ini menggunakan pendekatan kualitatif dan analisis literatur sebagai metode analisis data. Dengan demikian, untuk merespon pembelajaran virtual di masa pandemi COVID-19 maka perlu mengedepankan dan menerapkan pendidikan serta metode yang lebih mampu memahami kondisi manusia sebagai pembelajar. Diharapkan melalui proses itu, maka tujuan pendidikan secara umum dapat tercapai dan tujuan pembelajaran secara khusus dapat terwujud.